DESAIN DIDAKTIS MEDIA RODA PECAHAN UNTUK MENINGKATKAN PEMAHAMAN OPERASI PECAHAN PADA SISWA SEKOLAH DASAR - Afifah Dwi Ramadhani; Mhmd Habibi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Fractions are one of the basic principles in mathematics that have many applications in the real world. One of the problems in everyday life that is an application of fractional numbers is dividing cakes or pieces of fruit into equal amounts. So with the existence of fractional learning materials, it is hoped that students will be able to adapt a problem in everyday life with fractional learning. However, students' perceptions of mathematics as a difficult and boring subject make this subject the most feared by many elementary school students, so that it will have an impact on students' abilities that are far from expectations. This study used the Didactic Design Research (DDR) method with a qualitative approach. By adding attractive colors and images, students become more interested in learning about fractional operations. This can be seen from the enthusiasm of students in calculating the number of breads and watermelons that are still left as shown in the picture. Of course, with the increasing interest of students in following the learning material, it will increase students' ability to understand a learning material. Thus it can be concluded that students can more easily understand fractional operations if they use interesting media such as fractional wheel media.